2016
DOI: 10.1080/14330237.2016.1208929
|View full text |Cite
|
Sign up to set email alerts
|

Family structure and functioning: Influences on adolescents psychological needs, goals and aspirations in a South African setting

Abstract: This study aimed to determine the effects of family structure and functioning on basic psychological need fulfilment, life goals and aspirations of adolescents in a South African setting. Participants were 457 adolescent learners (Mage = 16.31, SD = 1.45, females = 54%, coloured = 56%) selected from four public schools in the Western Cape, South Africa. The adolescents completed the Family Assessment Device, Aspirations Index and Psychological Needs Scales. Results following multiple regression analysis sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The indirect effect test also demonstrated that, consistent with the hypothesis, perceiving the parents as need-supportive vitalizes the experience of needs satisfaction, and the experience of needs satisfaction leads to an increase in child's intrinsic values. These findings build on the existing findings of Davids et al. (2016), which found an association between needs satisfaction and intrinsic values and lend empirical support to the theoretical conjectures from both SDT (Kasser et al., 2014; Sheldon, Arndt, & Houser- Marko, 2003) and Rogers (1964) that the self is the integrative centre of an organism equipped with organismic valuing process and that needs satisfaction provides psychological energy to the self .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The indirect effect test also demonstrated that, consistent with the hypothesis, perceiving the parents as need-supportive vitalizes the experience of needs satisfaction, and the experience of needs satisfaction leads to an increase in child's intrinsic values. These findings build on the existing findings of Davids et al. (2016), which found an association between needs satisfaction and intrinsic values and lend empirical support to the theoretical conjectures from both SDT (Kasser et al., 2014; Sheldon, Arndt, & Houser- Marko, 2003) and Rogers (1964) that the self is the integrative centre of an organism equipped with organismic valuing process and that needs satisfaction provides psychological energy to the self .…”
Section: Discussionsupporting
confidence: 85%
“…Most of the studies that examined the associations between needs satisfaction (versus frustration) and intrinsic (versus extrinsic) values used a cross‐sectional research design (Davids, Ryan, Yassin, Hendrickse, & Roman, 2016; Lekes et al., 2011; Roest, Dubas, & Gerris, 2012), which only implies associations among variables and limits conclusions on the directionality of these associations. A more rigorous testing with a longitudinal design is warranted to clarify the strength and directionality of these associations.…”
Section: Possible Developmental Pathways Of Valuesmentioning
confidence: 99%
“…Thus far, we have demonstrated that individuals’ aspirations affect their own flourishing, and that aspirations can be shared among family members (Davids, Ryan, Yassin, Hendrickse, & Roman, 2016; Kasser et al, 1995; Kuczynski et al, 1997). What remains unclear is if the differential well‐being effects of intrinsic and extrinsic aspirations are also shared in families.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction in family functioning causes many psychological problems for family members (Yahyaee, Nooranipoora, Shafiabadia, & Farzad, 2015). Davids, Ryan, Yassin, Hendrickse, and Roman (2016) suggested that intact families predict higher satisfaction of basic psychological needs among adolescents than do nonintact families. Akwei (2015) revealed that adolescents from a functional family have higher psychological well-being and that parental conflict and adolescent psychological wellbeing are negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and Gans (2016) revealed that children's depressed and anxious behavior are related to their parents' individual cortisol response to family interaction. Davids, Ryan, Yassin, Hendrickse, and Roman (2016) suggested that intact families predict higher satisfaction of basic psychological needs among adolescents than do non-intact families. Likewise, Akwei (2015) revealed that adolescents from a functional family have high psychological well-being and that parental conflict and adolescent psychological well-being are negatively correlated.…”
Section: Theoretical Considerationsmentioning
confidence: 99%